Modified Lower Pole Autologous Dermal Sling for Implant Reconstruction in Women Undergoing Immediate Breast Reconstruction after Mastectomy - Pankaj G. Roy (International Journal of Breast Cancer)
Background. Autologous dermal sling with wise pattern skin reducing mastectomy allows one-stage implant reconstruction in women with large and ptotic breasts needing mastectomy for cancer or risk reduction. However, this technique is not suitable for women who lack ptosis and also carries risk of T-junction breakdown. Method. We have performed one-stage nipple sparing mastectomies with implant reconstruction in 5 women (8 breasts) by modifying the autologous dermal sling approach. All these women had small to moderate breasts with no ptosis or pseudoptosis. Results. Three women had bilateral procedures, two underwent bilateral mastectomies simultaneously, and one had contralateral risk reduction surgery a year after the cancer side operation. All women underwent direct to implant reconstruction with implant volumes varying from 320 to 375 cc. There were no implant losses and only one required further surgery to excise the nipple for positive nipple shaves. A low complication rate was encountered in this series with good aesthetic outcome. Conclusion. The modified lower pole dermal sling allows direct to implant reconstruction in selected women with small to moderate sized breasts with minimal ptosis. The approach is safe and cost-effective and results in more natural reconstruction with preservation of nipple.